FAKTOR-FAKTOR MOTIVASIONAL YANG BERPENGARUH TERHADAP PERILAKU KNOWLEDGE SHARING AUDITOR - Kainama, Maryoni S (Magister Manajemen Universitas Wisnuwardhana, 2019)
The purpose of this study is to identify and analyze the factors at the individual level that may affect the auditor auditor attitudes towards knowledge sharing behavior, which is expected to be able to add to our understanding of the behavior of interest and the factors underlying the increase or reduction of knowledge sharing behaviors performed by auditors . Necessary data is obtained by using a questionnaire containing grains measuring constructs of the variables used in the model study. Primary data were obtained at 153 answers from questionnaires filled out by auditors who work in public accounting firms registered with the Capital Market Supervisory Agency (BAPEPAM). Five proposed hypothesis proposed in this study, the first hypothesis which states that extrinsic motivation negatively affect the auditor's knowledge sharing attitudes, the second hypothesis states that the absorptive capacity has positive influence on the attitude of the auditor regarding knowledge sharing, the third hypothesis which states that organizational commitment has a positive effect the auditor's knowledge sharing attitudes, the fourth hypothesis which states that subjective norm has positive influence on the attitude of the auditor regarding knowledge sharing, and the fifth hypothesis which states that the sense of self-worth positive effect on the auditor's knowledge sharing attitude. This study is expected to provide practical implications for public accounting firms in order to encourage and increase the intensity of the behavior of knowledge sharing among employees by utilizing factors into the antecedents of knowledge sharing behavior. Public accounting firm can incorporate specific guidelines in their recruitment policies to enable them to recruit candidates that show characters that are consistent with the purpose and value of the company that will be associated with the ability to work in a team and a willingness to share knowledge Keywords: Knowledge sharing, Theory of reasoned action, Extrinsic Motivation, Absorptive capacity, Organizational Commitment, Sense of Self-Worth.